Malay translation and validation of modified checklist for autism in toddlers, revised with follow-up (M-CHAT-R/F) - Ariffin, R. A.; Ismail, J.; Abd Rahman, F. N.; Wan Ismail, W. S.; Ahmad, N.; Abdul Ghafar, A.; Yang, W. W.; Masra, F.; Kamal Nor, N. (Frontiers in Pediatrics, 2024)
Autism spectrum disorder (ASD) is one of the most common neurodevelopmental disorders in the pediatric population. The diagnosis is made clinically using diagnostic criteria such as the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). ASD is associated with significant social, emotional, and psychological impacts on affected children and their families. Early identification and diagnosis of ASD is crucial as it is linked to better outcomes and reduced adverse consequences. M-CHAT-R/F is a widely used, universally accepted, valid, and reliable tool that was developed to screen ASD cases as early as possible to enable prompt diagnosis and initiation of intervention. For communities that do not use English as their first language, reliable translation of M-CHAT-R/F to local languages is an important factor in ensuring good and effective screening and improving outcomes in children with ASD. To enhance ASD screening in Malaysia, the latest version of M-CHAT-R/F was translated into Malay and evaluated for reliability and validity.